Experimental measurement and prediction of ionic liquid ionisation energies. Issue 37 (21st September 2021) - Seymour, Jake M.; Gousseva, Ekaterina; Large, Alexander I.; Clarke, Coby J.; Licence, Peter; Fogarty, Richard M.; Duncan, David A.; Ferrer, Pilar; Venturini, Federica; Bennett, Roger A.; Palgrave, Robert G.; Lovelock, Kevin R. J.
Abstract : Non-resonant and resonant photoelectron spectroscopy was used to measure electronic structure descriptors for 60 ionic liquids, allowing the development of design rules to predict the electronic structure descriptors for a further 516 ionic liquids. Abstract : Ionic liquid (IL) valence electronic structure provides key descriptors for understanding and predicting IL properties. The ionisation energies of 60 ILs are measured and the most readily ionised valence state of each IL (the highest occupied molecular orbital, HOMO) is identified using a combination of X-ray photoelectron spectroscopy (XPS) and synchrotron resonant XPS. A structurally diverse range of cations and anions were studied. The cation gave rise to the HOMO for nine of the 60 ILs presented here, meaning it is energetically more favourable to remove an electron from the cation than the anion. The influence of the cation on the anion electronic structure (and vice versa ) were established; the electrostatic effects are well understood and demonstrated to be consistently predictable. We used this knowledge to make predictions of both ionisation energy and HOMO identity for a further 516 ILs, providing a very valuable dataset for benchmarking electronic structure calculations and enabling the development of models linking experimental valence electronic structure descriptors to other IL properties, e.g. electrochemical stability. Furthermore, we provide design rules for the prediction of the electronic structure of ILs.